Examining the liquidity risk of ASEAN banks by using partial adjustment model - Abdo, Khalil Yahya Mohammed (2016)
The aim of study is to examine whether ASEAN banks actively manage their liquidity or not and how effective the liquidity risk has been managed. Two liquidity measurements have been used, the first one is net stable funding ratio (NSFR) which indicates banks’ long-term liquidity buffer and the second one is the short-term liquidity ratio (SHORT). The study used annual data of 87 banks that operate in 6-ASEAN countries over 20-year period (1996-2015). Firstly, partial adjustment model is employed to examine whether ASEAN banks do have liquidity target ratios. The findings showed thatthe average estimated liquidity target for NSFR is 1.4936, and 0.6417 for SHORT. These findings confirm that ASEAN banks do have liquidity targets. Secondly, generalized method of moments (GMM) is employed to estimate the speed of adjustment of ASEAN banks towards their liquidity target ratios. The findings revealed that the adjustment speed for NSFR is 0.406 and 0.366 for SHORT, this implied that ASEAN banks adjust their NSFR quicker than their SHORT. Thirdly, GMM estimation method is used to examine the determinants of banks’ liquidity target ratios. The results showed that bank size was found positively related with NSFR and negatively with SHORT. Furthermore, equity ratio and asset quality negatively affected both NSFR and SHORT, while bank growth plan, funding cost and interest rate spread were positively influencing the liquidity targets for both NSFR and SHORT. In addition, GDP was found insignificant for both NSFR and SHORT. Fourthly, ordinary least squares (OLS) regression estimation technique is used to examine the determinants of ASEAN banks’ speed of adjustment toward liquidity. The results showed that the liquidity distance from target level (GAP) was positively related with the adjustment speed whereasbank size, GDP growth, and financial crises had negative impacts on the banks’ speed of adjustment. Lastly, OLS regression is used to examine the impact of speed of adjustment toward liquidity on banks’ profitability. The results showed that the liquidity’s speed of adjustment affected banks’ profitability negatively.